The Correlation Between Listening to English Songs and the Students’ Vocabulary Mastery - Kamila, Athiya; Amin, Fatimah Hidayahni; Novia, Lely (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research aimed to discover the correlation between the students’ likelihood of listening to English songs habit and their vocabulary mastery. This research engaged the correlational method by using a quantitative method. There are two variables in this research. Listening to English songs is variable X and The Students’ Vocabulary Mastery is variable Y. The students’ likelihood of listening to English songs was attained by distributing a questionnaire while the students’ vocabulary mastery was acquired from a test. The population consists of 228 students who registered active and are classified into four academic years, 2019, 2020, 2021, and 2022. The samples were selected using a random sampling technique. Based on the calculation, it was found that the mean score of the students’ likelihood of listening to English songs is 60.05. Meanwhile, the mean score of the students’ vocabulary mastery test is 37.7. The research data were calculated through SPSS 26. The correlation result of both variables is 0.24, which is interpreted as the strength of the correlation between the two variables gained constantly rated as significant at the weak level.